PEMBELAJARAN IPA MENGGUNAKAN MODEL PEMBELAJARAN BERBASIS PROYEK MELALUI METODE EKSPERIMEN LABORATORIUM UNTUK MENINGKATKAN HASIL BELAJAR DAN KREATIVITAS SISWA KELAS VIII.6 SMPS YPPI TUALANG - Eka Riendra, Meli Eka Riendra Meli; Syafii, Wan Syafii Wan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to improve learning outcomes and creativity of students in learning science to use Project Based Learning (PjBL) model and through laboratory experimental method in class VIII.6 SMPS YPPI Tualang. The research was conducted in July to October 2014. The parameters used in this study is the result of learning, creativity, and skills of students in practical performance, projects and products. The research instrument used was a learning device that consists of a lesson plans, syllabus, student worksheet, worksheet project, and instrument data capture form of learning about the test results, observation sheets for creativity and skill in the performance lab and assessment sheets for skills in project and product performance. The collected data were analyzed descriptively. The results showed that the absorption of students in the first cycle of 3.03 (B / Good) increased in the second cycle becomes 3.27 (B+/ Good). Mastery learning of individuals in the first cycle of 2.74 (B-/Good) increased in the second cycle becomes 3.78 (A-/ Very Good). Creativity of students in the first cycle is 47.31% or 1.89 (C / Enough) and increased in the second cycle into 61.00% or 2.44 (C+/ Enough). Student's skills in practical performance in the first cycle is 3.31 (B+/Good) increased in the second cycle is 3.58 (B+/Good). Students' skills in project performance in the first cycle is 3.33 (B+/Good) increased in the second cycle is 3.38 (B+/Good). Student's skills in the performance of the product in the first cycle is 3.33 (B+/Good) increased in the second cycle is 3.64 (A- / Very Good). It can be concluded that the model PjBL through laboratory experiment method can improve learning outcomes and creativity of science teaching biology class students VIII.6 SMPS YPPI Tualang. Keywords: Sains learning , PjBL, laboratory experimental, learning outcomes, creativity